Abstract Life : Practices of Abstraction in Deleuze, Whitehead and Bergson (Nóema, 2022)
In this paper I will argue that Deleuze, Whitehead and Bergson share a similar approach to abstraction, an approach that is fundamentally ‘pragmatist’ (broadly construed, close to James Williams’ ‘fantastic’ pragmatism). Leaning on William James one name for this shared approach methodologically is radical empiricism and is best understood in my view in the context of process philosophy. Although, they share a similar approach I will point out some differences between the radical empiricists in the way they think about some of their own key abstractions engaging the themes of relation, becoming and space-time. All three thinkers give us abstractions for thinking life as the creation of the new.
Keywords: Abstraction; Becoming; Empiricism; Life; Rhythm; Space; Time